2019
DOI: 10.1055/s-0039-3401046
|View full text |Cite
|
Sign up to set email alerts
|

“Door-In to Door-Out” Delay in Patients with Acute ST-Segment Elevation Myocardial Infarction Transferred for Primary Percutaneous Coronary Intervention in a Metropolitan STEMI Network of a Developing Country

Abstract: Routine performance measures of primary percutaneous coronary intervention (PCI) within an ST-segment elevation myocardial infarction (STEMI) network are needed to improve care.We evaluated the door-in to door-out (DI–DO) delays at the initial hospitals in STEMI patients as a routine performance measure of the metropolitan STEMI network.We retrospectively analyzed the DI–DO time from 1,076 patients with acute STEMI who were transferred by ground ambulance to a primary PCI center for primary PCI between 4 Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Similarly, a history of chronic angina was higher in women 64% than the 50% observed in men [37] . Women also had a lower probability of receiving proper treatment for STEMI than men in several studies [26] , [38] .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Similarly, a history of chronic angina was higher in women 64% than the 50% observed in men [37] . Women also had a lower probability of receiving proper treatment for STEMI than men in several studies [26] , [38] .…”
Section: Resultsmentioning
confidence: 89%
“…In the current study, the duration of time from symptom onset to first medical contact ranged from less than 10 min [14] to 96 h [15] with a mean of 12.7 h. In three studies, the focus was the delay between arrival to the emergency department and treatment initiation [16] perceptions of treatment urgency for ACS symptoms [17] and the overall time delay to treatment [18] . Four studies reported that all patients sought medical contact within 12 h of symptom onset [19] , [20] , [21] , [22] , while 26 studies reported treatment delays of 12 h or more, of these, 7 studies showed that at least 50% of the study population were delayed for 12 h until the initial medical contact [15] , [23] , [24] , [25] , [26] , [27] , [28] . Only 1 study by Sharma and colleagues [29] targeted characteristics of patients arriving over 12-hours from symptom onset to treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we were unable to define door-in-door-out (DIDO) time, it might have influenced SAT in the region with a short driving time. [ 14 , 24 ] Second, the optimal goal of SBT of STEMI might require a stricter value. The stratification of SBT <120, <180, and <360 minutes and setting a goal could strongly impact survival in patients with AMI.…”
Section: Discussionmentioning
confidence: 99%